Some sequence spaces of fuzzy numbers defined by Orlicz function (Acta Scientiarum. Technology, 2015)
In this article we introduce some fuzzy sequence spaces defined by Orlicz function and study different properties of these spaces like completeness, symmetricity etc. We establish some inclusion results among them.Â